Aplikasi Geographic Information System dan Remote Sensing untuk Pengembangan Potensi Wisata Agro di Kawasan Objek Wisata Air Terjun Tegenungan, Desa Kemenuh - PUTRA, WIRADHIKA MAHAYASA; LANYA, INDAYATI; ADI, I GUSTI PUTU RATNA (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022), 2022)
Wiradhika Mahayasa Putra. NIM. 1706541045. GIS Application and Remote Sensing for Agrotourism Potential Development In Tegenungan Waterfall Tourism Area, Kemenuh Village, Sukawati District. The implementation of agricultural and tourism activities is an agro-tourism concept can be synergized with other natural tourism objects such as waterfalls, Tegenungan Waterfall tourist attraction areas, Kemenuh Village, agro-tourism potential development can be carried out. The purpose of this research is to inform the area database based on GIS and remote sensing, identification and information on agro-tourism potential, mapping of tourist attractions and planning of locations for agro-tourism objects. Research methods: literature study, interpretation of satellite imagery, recording of information on potential tourist objects, calculation of the status of potential tourist objects,  recording of regional databases, identification of agro-tourism objects, calculation and division of potential classes,  mapping of tourist attractions. The results of this study indicate the value of the potential class of Tegenungan Waterfall tourism objects is in the good category with a value of 28. The map of the area displays a database of area, road length and land use, the value of the agro-tourism destination plan are classified as good with a value of 25, tourist information maps present an overview of tourist attractions at the location, the agro-tourism plan map displays the agro- tourism object plan:   rice field cycling, plowing, canang making, educational tours, banana and coconut biodiversity and subak view.